Transient benign unilateral dilated pupil after pathologic oral surgery under general anesthesia: A case report - Mohammad Mehdi Farahmand; Hosien Danesteh; Hosein Mohamadkhani; Hamid Reza Eftekharian (Elsevier, 2023)
We present a 33-year-old male case who underwent pathologic oral surgery. The mydriasis was completely resolved approximately 7 h after the end of the operation without any medical or surgical interventions. Neuro-ophthalmic exam showed that there was no ptosis or ophthalmoplegia. There was no clinical evidence for a Horner syndrome. Meticulous ophthalmological examination, especially pupillary examination, plays an important role in diagnosis and management of neurological disease.